READING COLONIZATION IN CONRAD'S TRANS-RACIAL LOVE PLOTS - Sandra Lilyana (Kajian Linguistik dan Sastra, 2005)
The study is about a close look at Conrad's trans-racial romance related to the Victorian period. Trans-racial love between white men and non-white women becomes a popular theme in the early works of Josep Conrad, a famous writer of the late Victorian period. Using a closely technical reading in the three of Conrad's works Lord Jim, Almayer's Folly, and An Outcast of the Island, we can show that such a trans-racial romance is not merely meant for appreciating equivalence. In turn, the trans-racial romance of Conrad's can be understood as the reflection of the Western colonization on the East where the white men take a role as subjects who had dominately explored while the non-white women as objects who are passively being explored.Key words: colonization, race, romance plot, subject, object, and dominance